BOOK REVIEW: SUNDAY’S SERMON FOR MONDAY’S WORLD. PREACHING TO SHAPE DARING WITNESS - M Laubscher (Acta Theologica)
Brown, S.A. (Grand Rapids, MI: Wm B. Eerdmans, 2020), 224pp. Price: R513. ISBN: 978-0-8028-7112-1 is reviewed by M. Laubscher.